Developing Number Puzzle Learning Media for Elementary School Dyslexic Students: Single Subject Research - Sumarno Ismail; Nursiya Bito; Franky Alfrits Oroh; Nisky Imansyah Yahya; Fuzi Sandra Talibo (Didaktik Matematika, 2023)
A child displaying symptoms of dyslexic learning disorders requires assistance in accurately identifying numbers, particularly those that share resemblances. This research aimed to develop media for teaching dyslexic children to help them identify numbers correctly.This research employed a development and single-subject research method.The subject was a child with symptoms of dyslexia learning disorders from primary school in Gorontalo, Indonesia. The research instruments used were observation sheets and media validation. The findings revealed that prior to engaging with the puzzle activity, the dyslexic student demonstrated the capability to identify a range of 4 to 5 numbers accurately. However, after participating in the puzzle activity, the dyslexic student exhibited an improved performance, achieving the ability to correctly recognize and recall 8 to 10 digits in both writing and memory. The number puzzle media was developed by dividing the puzzle into two parts: the part of the screen containing the complete picture and the base placing the puzzle pieces. The puzzle pieces were made by stacking several formed duplex parts, then covered with paper glued together to create a waterproof product. The puzzle focused on the numbers contrasting in color. The numbers were divided into several parts to make it easier for dyslexic students to identify models of these numbers. After conducting media testing on a dyslexic student, the analysis demonstrated a positive impact of the media on learning outcomes. This research suggests a notable improvement in the numerical identification skills of the dyslexic student